The University as Management Link with the Entrepreneurship and Innovation Ecosystems - Patino-Galvan, Israel (Archives of Business Research, 2025)
During the COVID-19 pandemic, nearly 2.7 million companies closed, and with-it unemployment worldwide increased 25%, 18.6% for The Organization for Economic Cooperation and Development (OECD-OCDE) and The Economic Commission for Latin America (ECLA-CEPAL) countries, and 26.9% for Mexico. Therefore, the workforce presented difficulties in assessing employment, which forced them as an option to join informal employment, which grew on average by 59% during the pandemic. Given this scenario, [1] [2] entrepreneurship is a a real alternative to create jobs and promote economic development. However, they require an ecosystem as a linking agent to collaborate with its materialization, permanence and success in the market. Therefore, a descriptive study was carried out applying to 384 public and private universities in the 32 states of Mexico, to identify the actors with which universities are linked through incubators